2018
DOI: 10.3389/fpsyg.2018.00627
|View full text |Cite|
|
Sign up to set email alerts
|

Better Cognitive Performance Is Associated With the Combination of High Trait Mindfulness and Low Trait Anxiety

Abstract: There are several ways in which cognitive and neurophysiological parameters have been consistently used to explain the variability in cognitive ability between people. However, little has been done to explore how such cognitive abilities are influenced by differences in personality traits. Dispositional mindfulness and anxiety are two inversely linked traits that have been independently attributed to a range of cognitive functions. The current study investigated these two traits in combination along with measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 100 publications
(176 reference statements)
5
33
1
Order By: Relevance
“…It is previously shown that mindfulness training increases the efficiency of the attention networks of orienting ( Jha et al, 2007 ) and conflict detection ( Wenk-Sormaz, 2005 ; Chan and Woollacott, 2007 ; Slagter et al, 2007 ; Tang et al, 2007 ; Moore and Malinowski, 2009 ; Ainsworth et al, 2013 ), and possibly the interaction between orienting and conflict detection ( Moore and Malinowski, 2009 ). However, only a few studies ( Josefsson and Broberg, 2011 ; Ainsworth et al, 2013 ; Di Francesco et al, 2017 ; Jaiswal et al, 2018 ) have investigated the effects of dispositional mindfulness on the same attention networks. We applied the FFMQ that measures dispositional mindfulness as a multi-faceted construct and measured the attention networks with the ANT-R allowing for studying the interaction between early operating orienting and conflict detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is previously shown that mindfulness training increases the efficiency of the attention networks of orienting ( Jha et al, 2007 ) and conflict detection ( Wenk-Sormaz, 2005 ; Chan and Woollacott, 2007 ; Slagter et al, 2007 ; Tang et al, 2007 ; Moore and Malinowski, 2009 ; Ainsworth et al, 2013 ), and possibly the interaction between orienting and conflict detection ( Moore and Malinowski, 2009 ). However, only a few studies ( Josefsson and Broberg, 2011 ; Ainsworth et al, 2013 ; Di Francesco et al, 2017 ; Jaiswal et al, 2018 ) have investigated the effects of dispositional mindfulness on the same attention networks. We applied the FFMQ that measures dispositional mindfulness as a multi-faceted construct and measured the attention networks with the ANT-R allowing for studying the interaction between early operating orienting and conflict detection.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between dispositional mindfulness and attentional control shows inconsistent results across the few studies that have been conducted ( Josefsson and Broberg, 2011 ; Ainsworth et al, 2013 ; Di Francesco et al, 2017 ; Jaiswal et al, 2018 ). These inconsistencies seem to stem from applying different versions of the Attention Network Test (ANT), which measures the three attention networks, and different approaches in measuring dispositional mindfulness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained here are consistent with motor inhibitory control being unaffected by mindfulness, irrespective of whether engagement with the technique is long or brief. Future mindfulness studies should investigate a broader spectrum of cognitive tasks and sample populations (Jaiswal et al, 2018) to test cognitive functions and population types that might be sensitive to mindfulness interventions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was shown that under a low cognitive load state, individuals with higher trait anxiety levels showed impaired conflict control (Bishop, 2009). Additionally, a recent study (Jaiswal, Tsai, Juan, Liang, & Muggleton, 2018) showed that when participants were grouped based on their mindfulness and anxiety scores, the group with high mindfulness and low anxiety had higher efficiency of cognitive control, reflected in higher accuracy on the Stroop task as well as in its associated electrophysiology (Jaiswal, Tsai, Juan, Muggleton, & Liang, 2019). They also showed higher visual working memory capacity on a change-detection task.…”
Section: Behavioral Measuresmentioning
confidence: 99%